Study on integrated farming systems model development - Bhuiya, MSU; Karim, MM; Hossain, SMA (Journal of the Bangladesh Agricultural University, 2016)
Study on Integrated Farming Systems Model Development was conducted by the Livelihood Improvement of Farming Community in Haor area through System approach Project of the Department of Agronomy, Bangladesh Agricultral University, Mymensigh worked in Purbo Tethulia village of Moahjganj upazilla, Netrakona district from April 2010 to June 2013 with the financial assistance from the National Agricultural Technology Project, SPGR subproject, Bangladesh Agricultural Council with the following objectives i. Increase productivity of field crops, vegetables, livestock and fishes in a household through the use of appropriate technogies and techniques devised/developed/ designed/refined by the farmers for ensuring household food security and nutritional upliftment and raising income ii. Diversify enterprises, mobilize resources and intensify farming and non farming activities for in situ employment generation iii. Conserve farm environment through efficient mobilization and management of natural resource for sustainable production sysyems iv. Develop human resoures for capacity building of the participants and improve their livelihood through system approach. Research programme was finalized in the Bench Mark Survey Workshop. Farmer selection for different research acivities was done as per plan for defferent five components. The crop and agroforestry component conducted experiments both in the homestead land and crop land. In the homestead area, year round vegetables were intervened through community trial for three years. Production of timber trees like mahogany, lambu and fruit trees like mango, guave, jujube, litchi, lemon papaya and jackfruit was also practiced. Timber trees are now at growing stage and among the fruit trees some like papaya, jujube and lemon are at bearing stage. African dhaincha was introduced around homestead fallow/waste land to protect homestead area from wave thrust and to produce biomass fuel. Field trials on rice, vegetables, spices and oil crops were conducted to intensify and diversify the cropping pattern and as well as to utilize the fallow/ waste land of the research site. Under livestock component, experiments were conducted on rearing of egg producing hen, duck, fattening of animals, milching cow, artificial insemination and chemical evaluation of available feedstuffs. A continuous vaccination programme against common diseases of poultry was maintained throughout the study period. Farmers response was very positive towards the experimental results. In the fisheries component, experiment on cage culture in open water, perennial and seasonal pond culture, dry fish and pickle were conducted/done. Among the experiments cage culture in open water proved to be a promising technology and fish pickle was highly appreciated in panel test. For the rural hydrology and mechanization component four studies were conducted. The physico-chemical properties of farm land and homestead soils were determined. Additional application of sulphur and zinc fertilizers were found not required. Both the surface and groundwater characteristics were studied. The maximum flood water depth was found around 3.0 m at farm land. Irrigation facilities developed by installing a shallow tubewell (STW) resulted higher crop production and motivated farmers to install four new STWs by their own capital. All the households (462) of Purbo Tethulia were intervened from the project. The interventions were crop, vegetable, livestock, poultry and fish farming. It was observed that as the number of enterprises increased in the farming systems, the income also increased. The evidence also showed that the training of the beneficiaries increased their knowledge and skill. J. Bangladesh Agril. Univ. 12(2): 325-336, December 2014